Pemahaman Mendalam tentang Kewirausahaan: Manfaat yang Diperoleh, Fungsi yang Dimainkan, dan Peran dalam Perubahan Sosial dan Ekonomi - Ninawati Ninawati; Veronika Tiara; Fransiska Liska; Yusawinur Barella (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
This research aims to determine the benefits, functions and role of entrepreneurship in improving the economy. This type of research is a qualitative description using literature study. Entrepreneurship is one of the organizations that helps in alleviating poverty. This research explores the various benefits, functions and roles of entrepreneurship in economic development. Data was collected from various secondary sources such as scientific journals, books, research reports, articles and relevant official publications. The findings show that entrepreneurship contributes significantly to job creation, innovation and improving community welfare. Apart from that, entrepreneurship also plays a role in encouraging local and national economic growth. The implications of this research indicate that entrepreneurship development must be supported through proactive policies and sustainable development to achieve maximum economic impact.